CRISPR/Cas9‐mediated homology donor repair base editing confers glyphosate resistance to rice (Oryza sativa L.) - Sony, Sonia Khan; Kaul, Tanushri; Motelb, Khaled Fathy Abdel; Thangaraj, Arulprakash; Bharti, Jyotsna; Kaul, Rashmi; Verma, Rachana; Nehra, Mamta (Frontiers in Plant Science, 2023)
Globally, CRISPR/Cas9-based genome editing has ushered in a novel era of crop advancements. Weeds pose serious threat to rice crop productivity. Amongst the numerous herbicides, glyphosate (N-(phosphonomethyl)-glycine) has been employed as post-emergent, broad-spectrum herbicide that represses the shikimate pathway via inhibition of EPSPS (5'-enolpyruvylshikimate-3-phosphate synthase) enzyme in chloroplasts. Here we describe the development of glyphosate-resistant rice lines by site-specific amino acid substitutions (G172A; T173I; P177S: GATIPS-mOsEPSPS) and modification of PEP binding site in the native OsEPSPS gene employing fragment knockout and knock-in of homology donor repair (HDR) template harbouring desired mutations through CRISPR-Cas9-based genome editing. The indigenously designed two-sgRNAOsEPSPS-NICTK-1_pCRISPR-Cas9 construct harbouring rice codon-optimized SpCas9 along with OsEPSPS-HDR template were transformed into rice. Stable homozygous T2 edited rice lines revealed significantly high degree of glyphosate-resistance both in vitro (4mM/L) and field conditions (6ml/L; RR) in contrast to wild-type (WT). Edited T2 rice lines (ER1-6) with enhanced glyphosate resistance revealed lower levels of endogenous shikimate (14.5-fold) in contrast to treated-WT but quite similar to WT. ER1-6 lines exhibited increased aromatic amino acid contents (Phe: 2-fold, Trp: 2.5-fold, and Tyr: 2-fold) than WT. Interestingly, glyphosate-resistant Cas9-free EL1-6 ¬rice lines displayed a significant increment in grain yield (20-22%) in comparison to WT. Taken together, results highlighted the efficacy of GATIPS mutations in OsEPSPS has tremendously contributed in glyphosate resistance (foliar spray of 6ml/L), enhancement of aromatic amino acids and improved grain yields in rice. These results ensure a novel strategy for weed management without yield penalties, with higher probability of commercial release.